Representation of a Perceptual Event in an Interview with an Artist - T. I. Petukhova; A. O. Chupakhina (Дискурс, 2023)
Introduction. The purpose  of the research is to consider  the linguistic actualization of the main characteristics of the artist's visual perception in the interview discourse. The relevance of the research is due to its inclusion in the context  of modern anthropo-oriented study of cognition of the world by a creative person.  The novelty of the research lies in the fact that for the  first time  the  process  of perception  of the  world by an English-speaking artist  is studied as an event within the framework of a complex  linguistic and cognitive approach, which allows to analyze its specificity to the fullest extent.Methodology and sources. The methodological  basis of the research was made up of the works   of   the    linguists-cognitologists    L.V.    Laenko,   I.Yu.   Kolesov,   psychologist    V. A. Barabanshchikov who revealed distinctive characteristics of perceptual image and substantiated  the  expediency   of  perception   as  an  event.  The  research  material   was interviews  with English-speaking  artists  from  the  Internet  versions  of  the  newspapers devoted  to  the  life and work of modern  artists.  The methods  of lexico-semantic, frame, contextual  and pragmalinguistic analysis were used.Results and discussion. The article reveals the peculiarities of visual perception  of the world by contemporary English-speaking artists, which are reflected in the discourse of the interview. The author  reveals  the multidimensionality of a subject  of perception,  different  ways of its representation on the verbal level: as an observer-actor and as a “offscreen” observer.  The paper shows the specificity of visual perception of the world by the artist as a perceptual event that  possesses spatial  and  temporal  coordinates  and  such  significant  characteristics  as dynamism, motivation, focus and emotionality. The denotative situation of perception is actualized in English by personal  pronouns,  active-action  predicates,  perceptual  predicates, existential constructions, phase verbs, and state change predicates.  The important feature  of the artist's creative perception  of the world is the forming of the necessity  of representation in his  consciousness perceptive  image  by means  of  painterly  signs.  As  a  result  of  such representation the given perceptive  image receives  the further  development  and becomes the basis for creating an artistic image to be embodied in an art work.Conclusion. In the interview with the artist there  is a complex process  of cognition of the world  by  the   creative   person,   based   on  the   perceptual   event.   Visual  perception   is represented by the artist as a directed activity, which is to learn and which requires  certain efforts  and motivation. As a result of the perceptual  event that the artist experiences, an artistic image is formed that is actualized in the work of art.